How to read journal articles in the social sciences - Shon, Phillip C. (London ; Thousand Oaks, Calif. : SAGE, 2012)
"Using a reading code sheet developed by the author, this book teaches students how to approach social and behavioral science journal articles as texts that can be deciphered structurally, mechanically, and grammatically. The included reading code sheet and reading strategies will allow students and researchers to systematize the reading, note-taking, and organizing of voluminous amounts of information in an easily identifiable and retrievable format, and will be a huge confidence boost to those who struggle with this first phase in the writing process."--pub. desc.
Serial killers and book reports -- Trying to fix mechanical and structural writing problems with abstract tools -- Three types of stains and false assumptions about writing -- Should I even read this? How to read the abstract, general introduction, and methods section -- So what? How to read the general literature review, psychology introductions, and results section -- Becoming a part of the scholarly community: how to read the discussion and conclusion -- Highlighting and organizing the ROF, SPL, CPL, GAP, RFW, and POC -- Will the reading code sheet work on non-social science texts? -- Concluding remarks.
Keywords: Social sciences; Reader-response criticism